2023
DOI: 10.1111/jir.13023
|View full text |Cite
|
Sign up to set email alerts
|

Training support workers about the overmedication of people with intellectual disabilities: an Australian pre–post pilot study

Abstract: Background There is evidence that psychotropic medications are overprescribed and overused to manage behaviours of concern for people with intellectual disabilities. Disability support workers and support staff lack education and training on the administration and safety of psychotropic medication use. This study aimed to test the applicability and preliminary efficacy of SPECTROM, an education programme developed in the UK, in an Australian context. MethodsThe training comprises two parts: Module 1 encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To address the issue of caregiver training, we have recently developed an online training resource backed up by face-toface workshops (SPECTROM; https://spectrom.wixsite.com/project) to help rationalise antipsychotics and other psychotropic medications (Deb et al, 2020). Two small pre, and post-intervention pilot studies of SPECTROM training in the United Kingdom (Deb et al, 2021) and Australia (Barratt et al, 2023;Wilson et al, 2022Wilson et al, , 2023 have received good feedback from the trainees and the trainers on the acceptability, practicality, applicability and relevance of SPECTROM to their practice and helped to empower support staff by increasing their knowledge of psychotropic medication and improving attitude toward using medication for challenging behaviour. Some participants in the current study found input from local pharmacists and nurse prescribers helpful in implementing STOMP.…”
Section: Discussionmentioning
confidence: 99%
“…To address the issue of caregiver training, we have recently developed an online training resource backed up by face-toface workshops (SPECTROM; https://spectrom.wixsite.com/project) to help rationalise antipsychotics and other psychotropic medications (Deb et al, 2020). Two small pre, and post-intervention pilot studies of SPECTROM training in the United Kingdom (Deb et al, 2021) and Australia (Barratt et al, 2023;Wilson et al, 2022Wilson et al, , 2023 have received good feedback from the trainees and the trainers on the acceptability, practicality, applicability and relevance of SPECTROM to their practice and helped to empower support staff by increasing their knowledge of psychotropic medication and improving attitude toward using medication for challenging behaviour. Some participants in the current study found input from local pharmacists and nurse prescribers helpful in implementing STOMP.…”
Section: Discussionmentioning
confidence: 99%
“…This paper solely presents rich qualitative data from post‐intervention interviews. Outcomes data is presented in a separate paper (Wilson et al, 2023). As this aspect of the study was exploratory in nature, a qualitative research design using individual interviews was utilised (Beail & Williams, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Forty-two participants received SPECTROM training in a recent Australian pre-post pilot study (Wilson et al, 2023). PKQ-R scores showed statistically significant post-training improvement at all post-training time points (p < 0.05).…”
Section: Spectrom Pilot Studiesmentioning
confidence: 96%